How to break a dragon's heart : the heroic misadventures of Hiccup the Viking - Cowell, Cressida (New York : Little, Brown, 2011)
Hiccup, stranded with Toothless on the Beach of the Broken Heart and being hunted by an old enemy, faces Ug the Uglithug, Berserks, and Scarers and tries to save Fishlegs from the Beast.
6.9
3-6
Keywords: Dragons -- Juvenile fiction; Vikings -- Juvenile fiction; Dragons -- Fiction; Vikings -- Fiction; Dragons -- Fiction; Vikings -- Fiction